Integrated Four Comparative-Omics Reveals the Mechanism of the Terpenoid Biosynthesis in Two Different Overwintering Cryptomeria fortunei Phenotypes - Zhang, Yingting; Cui, Jiebing; Hu, Hailiang; Xue, Jinyu; Yang, Junjie; Xu, Jin (Frontiers in Plant Science, 2021)
Chinese cedar (Cryptomeria fortunei) is a tree species with important ornamental, medicinal and economic value. Terpenoids extracted from the essential oil of C. fortunei needles have been considered valuable ingredients in the pharmaceutical and cosmetic industries. However, the possible gene regulation mechanisms that limit terpenoid biosynthesis in this genus are poorly understood. Here, we adopted integrated metabolome analysis, transcriptome, small-RNA (sRNA) and degradome sequencing to analyse the differences in terpenoid regulatory mechanisms in two different overwintering C. fortunei phenotypes (wild-type and an evergreen mutant). A total of 1447/6219 differentially synthesized metabolites (DSMs)/unigenes (DEGs) were detected through metabolome/transcriptome analyses, and these DSMs/DEGs were significantly enriched in flavonoid and diterpenoid biosynthesis pathways. In C. fortunei needles, 587 miRNAs, including 67 differentially expressed miRNAs (DERs), were detected. Among them, 8346 targets of 571 miRNAs were predicted using degradome data, and a 72-miRNA-target regulatory network involved in the metabolism of terpenoids and polyketides was constructed. Forty-one targets were further confirmed to be involved in terpenoid backbone and diterpenoid biosynthesis, and target analyses revealed that two miRNAs (i.e., aly-miR168a-5p and aof-miR396a) may be related to the different phenotypes and to differential regulation of diterpenoid biosynthesis. Overall, these results reveal that C. fortunei plants with the evergreen mutation maintain high terpenoid levels in winter through miRNA-target regulation, which provides a valuable resource for essential oil-related bioengineering research.